INVESTIGATION OF MICROBIAL COUNT IN THE SOIL AND EARTHWORM GUT (EUDRILUS EUGENIAE) - V, TAMIZHAZHAGAN; K, PUGAZHENDY; V, SAKTHIDASAN; K, REVATHI; M, BARANITHARAN (Innovare Journal of Agricultural Sciences, 2016)
ABSTRACT The soil microbes are highest in compared with earthworm gut of Eudrilus eugeniae. Microbes are soaring numbers of present in middle gut and several nutrients are gift within the soil. In soil, including pH, nitrogen, phosphorus, potassium, zinc, manganese, iron and copper. Earthworm gut from E. eugeniae compared with soil contains highest bacterium and fungi. E. eugeniae gut and soil present in the bacterial colony (Total count - 787.33; Per cent – 78.7%); fungal colony (Total count – 610.66; Per cent – 61.0 %). From the results it can be terminated the bacterial populations was a lot of within the soil and midgut region of E. eugeniae. Keywords: Soil, Earthworm gut, Bacteria, Fungi and Eudrilus eugeniae